An evaluation of risk mitigation strategies through prohibiting corruption, fraudulent, coercion and collusive practices in public procurement act, 2006 : a study on directorate of primary education - Islam, Md. Aminul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.